The Problem of Water Scarcity in Central Asia: the Factor of Afghanistan - S. S. Zhiltsov (Проблемы постсоветского пространства)
The article deals with the problem of water scarcity in the countries of Central Asia. Despite their efforts, the lack of water availability continues to persist. This increases tension in the inter-state relations in the region, as in recent years the countries increasingly face a shortage of water. Recently, Afghanistan has begun to influence the distribution of water resources in the region. Its actions are aimed at increasing abstraction of water resources from transboundary rivers of Central Asia. At the same time, Afghanistan has a right to act in this way. However, given the increasing shortage of water resources, Afghanistan’s policy may lead to new conflicts and exacerbation of relations with the Central Asian states.